2020
DOI: 10.3390/pr8020176
|View full text |Cite
|
Sign up to set email alerts
|

The Demulsification Properties of Cationic Hyperbranched Polyamidoamines for Polymer Flooding Emulsions and Microemulsions

Abstract: Polymer flooding emulsions and microemulsions caused by tertiary oil recovery technologies are harmful to the environment due to their excellent stability. Two cationic hyperbranched polyamidoamines (H-PAMAM), named as H-PAMAM-HA and H-PAMAM-ETA, were obtained by changing the terminal denotation agents to H-PAMAM, which was characterized by 1H NMR, FT-IR, and amine possession, thereby confirmed the modification. Samples (300 mg/L) were added to the polymer flooding emulsion (1500 mg/L oil concentration) at 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…According to the colloidal stability theory [23][24][25], when the absolute value of the ζ potential was more than 30 mV, it showed that the emulsified liquid was relatively stable. It showed very strong electronegativity according to the negative value of ζ, which indicated that the L-MWFs were emulsified by an anionic surfactant [2], and the residual oil drops of the L-MWFs formed stable interfacial films through anionic surfactants so that the oil was evenly dispersed in water.…”
Section: Properties Of the L-mwfsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the colloidal stability theory [23][24][25], when the absolute value of the ζ potential was more than 30 mV, it showed that the emulsified liquid was relatively stable. It showed very strong electronegativity according to the negative value of ζ, which indicated that the L-MWFs were emulsified by an anionic surfactant [2], and the residual oil drops of the L-MWFs formed stable interfacial films through anionic surfactants so that the oil was evenly dispersed in water.…”
Section: Properties Of the L-mwfsmentioning
confidence: 99%
“…Metalworking fluids (MWFs), which are a complex of oiling, surfactants and a variety of functional additives in accordance with a certain proportion of fusion, are abundantly utilized in the manufacturing domain and exert outstanding cooling, lubrication, anti-rust and anticorrosion protection functions [1,2]. Practically, after a long duration of repeating, attributed to the oil emulsion, residual metal chips, bacteria and the mix foreign material, the MWFs will gradually age, deteriorate and corrupt [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, hyperbranched polymers have various applications in many fields [4] including chemistry, life science, biotechnology, and the petroleum industry. Their applications in the petroleum industry include demulsifiers [5], corrosion and scale inhibitors [6], oil spill dispersants [7], and asphaltene dispersants [8]. HBPs consist of a central core spread out to form a network of repeating branches ended by characteristic groups, which form an external surface of the polymeric nanoparticle.…”
Section: Introductionmentioning
confidence: 99%